Multichannel quantum system of fiber-optics secure communication - Барановский, Олег Константинович; Гулаков, Иван Романович; Василиу, Евгений Викторович; Зеневич, Андрей Олегович; Лимарь, Игорь Валерьевич (Ukrainian Scientific Journal of Information Security, 2016)
The method and the scheme of multichannel quantum system of secure communication for transfer of confidential data on optical fiber are developed. The considered scheme combines quantum key distribution with quantum secure data transmission. Such approach does not give possibility to the eavesdropper to decipher that part of information, which he can receive before the detection. The suggested scheme provides higher security level of transferred confidential information, than known, which use traditional pro-tocols of symmetric enciphering in a combination to quantum key distribution. It is found out that for the transmission protected in such a way on optical fiber the choice of wavelengths of 850 and 1625 nanometers is optimum. It is found out that when using in such systems of the avalanche photo diode FD-115L it is possible to provide a speed of information transfer up to 0,8 Mbps in one channel. For increase in speed of transfer, it is proposed to use two and more channels of transfer.